On the strong convergence for weighted sums of negatively superadditive dependent random variables - Bing Meng; Dingcheng Wang; Qunying Wu (Journal of Inequalities and Applications, 2017)
Abstract In this article, some strong convergence results for weighted sums of negatively superadditive dependent random variables are studied without assumption of identical distribution. The results not only generalize the corresponding ones of Cai (Metrika 68:323-331, 2008) and Sung (Stat. Pap. 52:447-454, 2011), but also extend and improve the corresponding one of Chen and Sung (Stat. Probab. Lett. 92:45-52, 2014).